Actinomycotic osteonecrosis of the maxilla as a post-covid sequelae: A case report - V Vasanthi; Selvakumar Thulasiraman; Rajkumar Krishnan; Annasamy Ramesh Kumar (Oral Oncology Reports)
Osteonecrosis of the jaw refers to the necrosis of jaw bones due to compromised blood supply to the bone primarily from radiation, medication, trauma, infection, and malignancy. COVID-19 virus was found to bind to human ACE2 receptors and cause various systemic complications that have led to millions of deaths. The dysregulated immune response from COVID-19 infection predisposes patients to opportunistic infections. Actinomyces are filamentous, branching, anaerobic, gram-positive bacteria residing in the oral cavity as normal commensals. The breakdown of the mucosal barrier increases the risk of infection and invasion to deeper tissues. We present a case of actinomycotic osteonecrosis of the maxilla as a post-covid sequelae in a diabetic female patient.